Pengaruh Lingkungan Kerja Non Fisik, Reputasi Perusahaan dan Komitmen Afektif terhadap Keterikatan Karyawan pada PT. Wulandari Bangun Laksana Tbk - Nadia , Beril; Santoso, Bowo (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Evaluation of a company's success can depend on the effectiveness of its human resource management. One of the main objectives of this management is to foster employee involvement, as it has been shown that when employees develop a sense of attachment to the workplace, they tend to exert their best efforts in carrying out tasks to the best of their abilities. This research aims to determine the influence of the non-physical work environment, company reputation, and affective commitment on employee engagement at PT. Wulandari Bangun Laksana Tbk. The research method applied is a quantitative research method. The samples in this research were employees of the project division and HRD&GA at PT. Wulandari Bangun Laksana Tbk. The sampling technique used a saturated sampling method with 37 respondents obtained by distributing questionnaires. The data analysis technique uses Partial Least Square (PLS) software. The research results explain that the variables of non-physical work environment, company reputation, and affective commitment positively and significantly influence employee engagement at PT. Wulandari Bangun Laksana Tbk.